A Method to Determination of Lead Ions in Aqueous Samples: Ultrasound-Assisted Dispersive Liquid-Liquid Microextraction Method Based on Solidification of Floating Organic Drop and Back-Extraction Followed by FAAS - Çiğdem Arpa; Itır Aridaşir (Journal of Analytical Methods in Chemistry)
Ultrasound-assisted dispersive liquid-liquid microextraction method based on solidification of floating organic drop and back-extraction (UA-DLLME-SFO-BE) technique was proposed for preconcentration of lead ions. In this technique, two SFODME steps are applied in sequence. The classical SFODME was applied as the first step and then the second (back-extraction) step was applied. For the classical SFODME, Pb ions were complexed with Congo red at pH 10.0 and then extracted into 1-dodecanol. After this stage, a second extraction step was performed instead of direct determination of the analyte ion in the classical method. For this purpose, the organic phase containing the extracted analyte ions is treated with 1.0 mol·L−1 HNO3 solution and then exposed to ultrasonication. So, the analyte ions were back-extracted into the aqueous phase. Finally, the analyte ions in the aqueous phase were determined by FAAS directly. Owing to the second extraction step, a clogging problem caused by 1-dodecanol during FAAS determination was avoided. Some parameters which affect the extraction efficiency such as pH, volume of extraction solvent, concentration of complexing agent, type, volume, and concentration of back-extraction solvent, effect of cationic surfactant addition, effect of temperature, and so on were examined. Performed experiments showed that optimum pH was 10.0, 1-dodecanol extraction solvent volume was 75 μL, back-extraction solvent was 500 μL, 1.0 mol·L−1 HNO3, extraction time was 4 min, and extraction temperature was 40°C. Under optimum conditions, the enhancement factor, limit of detection, limit of quantification, and relative standard deviation were calculated as 81, 1.9 μg·L−1, 6.4 μg·L−1, and 3.4% (for 25 μg·L−1 Pb2+), respectively.